The Association Between Exercise Habit and Incidence of Hypertension Among Patients over 45 Years Old - Librianti Putriastuti (Universitas Airlangga, 2016)
Hypertension is a non-communicable disease that is estimated to cause 7.5 million deaths, around 12.8% of all deaths. This study aims to analyze the relationship between exercise habits and the incidence of hypertension in patients aged 45 years and above. This type of research is an analytic observational study with cross-sectional study design. The study was conducted on 97 patients who visited the Public health center (PHC) of Kedurus, Surabaya in May 2015 using systematic random sampling techniques. The dependent variable in this study was hypertension, while the independent variables were exercise status, exercise frequency, and exercise time. Data analysis using the chi-square test. The results showed that the incidence of hypertension was mostly suffered by respondents in the middle age category (45–59 years) (52.8%), female gender (80.6%), and had a high school / equivalent final education (26, 4%). The results showed a significant relationship between sports status and the incidence of hypertension (p = 0.001). The frequency of exercise (p = 0.068) and length of exercise (p = 0.710) did not have a significant relationship with the incidence of hypertension in patients aged 45 years and above, so it can be concluded that only the exercise status is related to the incidence of hypertension in patients aged 45 years and above. Therefore, the people especially those aged 45 years and over need to do blood pressure checks and exercise regularly to reduce the risk of hypertension.